Identifying reproductive events using archival tags: egg‐laying behaviour of the small spotted catshark Scyliorhinus canicula. Issue 1 (5th November 2012) - Wearmouth, V. J.; Southall, E. J.; Morritt, D.; Sims, D. W.
<x xml:space="preserve">Abstract</x> The use of archival depth telemetry as a means of remotely assessing the reproductive rates of free‐ranging fishes is explored. This is achieved by electronically tracking the vertical movements of individual female small spotted catsharks Scyliorhinus canicula in the natural environment, whilst simultaneously evaluating the temporal and vertical distributions of egg‐laying in this species. Distinctive patterns of short‐term (0·3–3·7 h), shallow‐water activity are documented in the time–depth profiles of female S. canicula that occur at an appropriate depth (1·0–2·3 m) and periodicity (every 10–12 days) to represent egg‐laying behaviour. Putative egg‐laying behaviour was exhibited simultaneously by two individually tracked female S. canicula during late‐spring and early‐summer. The results highlight that, provided species behaviour is suitable and complementary methods such as previous data, laboratory experiments and field surveys can be used to validate the patterns observed, archival depth telemetry offers an unobtrusive means by which egg production and egg‐laying behaviour of free‐living fishes can be estimated. As precise information regarding life‐history parameters is difficult to obtain for free‐ranging fish species, this technique could be used to improve the parameterization of species demographic models that are relevant to the management of wild fish populations.